Optimization of Microwave Heating and Ambient Tempering for Accelerated Drying of Milk Paneer Using Response Surface Methodology - Ahirwar, Shashi Bala; Verma, Devendra Kumar; Singh, Mohan; Daheriya, Mahendra; Maravi, Archna (International Journal of Bio-resource and Stress Management, 2023)
The study was conducted during January to June, 2019 under college of Agricultural Engineering, Department of Post Harvest Process and Food Engineering, JNKVV, Jabalpur, M.P. (482002), India. The main objective of the research was to determine how paneer cube size influenced drying time and to study the effect of the combination of microwave heating tempering time and hot air drying on drying rate of paneer cube. A paneer sample was prepared using a National Dairy Development Board-developed industrial paneer manufacturing procedure (NDDB). Response surface methodology was implemented in this study to optimize microwave heating and ambient tempering for accelerated drying of milk paneer. Optimization factors included paneer cube size (5–25 mm), microwave power level (150–750W), heating time (2–10 min), and tempering time (1–5 min), while responses included moisture content (dry basis %) and bulk density (g cc-1). Optimum parameter for highly acceptable product with (13.8 mm) cube size at the microwave power level (670.27 W), heating time (7.2 min), tempering time (4.621 min) presented the Moisture content (22.15%) and bulk density (0.36 g cc-1) by using Design expert 13. The experimental values under the microwave drying condition matched the outcome predicted by analysis of variance. It shows that the model is highly fit and that response surface methodology (RSM) was successful in maximizing the microwave power level, which has a significant and advantageous impact on drying rate.